PERLINDUNGAN HUKUM ANAK LUAR PERKAWINAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TERHADAP PUTUSAN NOMOR 109/PDT/2022/PT BTN - Kusumawati, Erlinda Yan; Cahyaningsih, Diana Tantri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
AbstractThis article aimed to explain and review about the legal protection of non-marital children after the Constitutional Court Decision Number 46/PUU-VIII/2010 against the Court Decision Number 109/PDT/2022/PT BTN. This article is a normative legal research. Sources of data are primary and secondary legal materials. The technique for collecting legal material is a library research. The approaches are statutory approach and conceptual approach. The legal material analysis technique uses qualitative analysis and syllogisms methodes using a deductive mindset. The result is that the legal protection of non-marital children before the Constitutional Court Decision 46/PUU-VIII/2010 was through the ratification and registration of the marital status of the child’s parents and child's birth, while after the Constitutional Court Decision Number was not based on the recording and ratification, but it has provided certainty and legal protection for non-marital children even though the validity of the marriage of the parents is still uncertain. In Court Decision Number 109/PDT/2022/PT BTN the Judge has violated and did not apply the Constitutional Court Decision according to the substance, so there is no legal certainty regarding the protection of non-marital children.AbstrakArtikel ini bertujuan untuk menjelaskan dan mengkaji terkait perlindungan hukum anak luar perkawinan pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 terhadap Putusan Nomor 109/PDT/2022/PT BTN. Artikel ini merupakan penelitian hukum normatif. Sumber data berupa bahan hukum primer dan sekunder. Teknik pengumpulan bahan hukum berupa teknik studi kepustakaan. Pendekatan dalam artikel ini adalah pendekatan perundang-undangan dan konseptual. Metode berpikir menggunakan analisis metode kualitatif dan penalaran (silogisme) dengan menggunakan pola pikir deduktif. Hasil dari artikel ini ialah bahwa perlindungan hukum anak luar perkawinan sebelum adanya Putusan Mahkamah Konstitusi 46/PUU-VIII/2010 ialah melalui pengesahan dan pencatatan status perkawinan orang tua dan kelahiran anak, lalu pasca Putusan Mahkamah Konstitusi Nomor bukan didasarkan pada pencatatan dan pengesahan tersebut melainkan memberikan kepastian dan perlindungan hukum bagi anak luar perkawinan walaupun keabsahan dari perkawinan orang tuanya masih belum pasti. Pada Putusan Nomor 109/PDT/2022/PT BTN hakim melanggar dan tidak menerapkan Putusan Mahkamah Konstitusi sesuai substansinya, sehingga tidak ada kepastian hukum pada perlindungan anak luar perkawinan.